2001
DOI: 10.2166/wst.2001.0226
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment of anaerobic effluents in constructed wetland systems

Abstract: This papers describes the behaviour of wetlands as a post-treatment unit for anaerobically treated sewage for the removal of organic matter, suspended solids, nutrients (nitrogen and phosphorus) and faecal coliforms. Raw sewage was treated in a UASB reactor with a retention time of 5 h and the effluent was used in four units of wetlands with coarse sand as the medium and operated with different hydraulic loads. Three of the units had emerging macrophytes (Juncus sp), whereas the fourth one was operated as a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 0 publications
0
15
2
5
Order By: Relevance
“…Results of the 1-year research developed by Sousa et al (2001), with a UASB/constructed wetland system, showed average COD removal efficiencies in the range of 79-85%, suspended solids in the range of 48-71% and faecal coliforms around 4 log-units. Phosphorus was also efficiently removed (average of 90% for the lowest hydraulic load) but nitrogen removal was only partial (45-70% for ammonia and 47-70% for TKN).…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…Results of the 1-year research developed by Sousa et al (2001), with a UASB/constructed wetland system, showed average COD removal efficiencies in the range of 79-85%, suspended solids in the range of 48-71% and faecal coliforms around 4 log-units. Phosphorus was also efficiently removed (average of 90% for the lowest hydraulic load) but nitrogen removal was only partial (45-70% for ammonia and 47-70% for TKN).…”
Section: Constructed Wetlandsmentioning
confidence: 99%
“…Purification efficiencies of BOD 7 , N tot and NH 4 -N responded negatively to the increases in hydraulic loading rates, and positively to the enhancing of recirculation rate, whereas the purification efficiency of P tot only showed a positive response to enhanced recirculation rate in the LWA system, and was not affected by the changes in the hydraulic loading rates.…”
Section: Discussionmentioning
confidence: 91%
“…The number of water samples per operational regime (1-6) varied in the following order: 1 st -4 samples, 2 nd -11 samples, 3 rd , 4 th and 5 th -9 samples each, and 6 th -11 samples. In the laboratory of the AS Tartu Veevärk, water samples were analyzed for BOD 7 , TSS, COD, N tot , NH 4 -N, NO 2 -N, NO 3 -N, P tot using Standard Methods for the Examination of Water and Wastewater [47]. * summarized recirculation rates from outflow and interim well were used in correlation analysis.…”
Section: Water Sampling and Analysismentioning
confidence: 99%
See 2 more Smart Citations